Maxmeta: aplicação para controle financeiro e alcance de metas - Soares, Marilia de Lima (Brasil, 2024)
People find it difficult to organize their finances, where they often fail to achieve their goals because there is no planning and/or control of their personal expenses. The lack of financial control to achieve goals reflects the lack of computational tools aimed at managing personal goals to deal with expenses or debts, directly impacting the achievement of personal goals. This work aims to develop a web system as a support tool in the planning and control of personal goals. To build and organize the production of this project, a set of activities and practices were adopted, the main ones being: project management, requirements gathering, Lean Inception for building the product backlog and MVP, system design, testing and implementation. The system was fed by users through registration data such as expenses, income and goals. It is expected that through this tool, with simple and intuitive usability features, users will be able to monitor and visualize progress and reach their goals with a maximum value of up to 20 minimum wages.